Analysis of Speech Acts in the Advertising Language of Yakult Beverage Products on Television - Datika Azzahra Prasetya; Intan Sari Ramdhani (CV. Rayyan Dwi Bharata, 2023)
Speech act events are usually used to find out certain information, speech act events are marked by the presence of speakers and speech partners. The problems studied in this analysis are speech acts, locutions, illocutions and perlocutions contained in the advertisement for Indomie instant noodles on television. This research is important because in a production, advertising is an important aspect to boost product sales. The implementation of this study used a qualitative descriptive method with a pragmatic approach, the data from this study were the language of indomie instant noodle advertisements which were written and then analyzed. Data collection techniques used observing and note-taking techniques. Data was obtained by viewing and observing Indomie instant noodle advertisements, then recording data from the advertisements to be studied. The results of this study indicate that there are events of locutionary speech acts, illocutionary speech acts and perlocutionary speech acts.